Potential Effects of Electronic Cigarette Vapour on Isolated Lung Cells and in Mouse Lungs - Roxlau, Elsa Tadele; Justus Liebig University Giessen (My University, 2019)
Cigarette smoking (CS) is the main preventable cause of chronic obstructive pulmonary disease (COPD) and lung cancer. Research of potentially less harmful nicotine delivery devices and tools for smoking cessation resulted in the development of electronic cigarettes (e-cigarette). Despite the lack of appropriate studies regarding their safety, efficacy and health effects, e-cigarettes are gaining popularity as an approach of CS cessation and the number of e-cigarettes users is rapidly growing worldwide, especially among younger generations. Against this background, the aim of the current study was to investigate the effects of e-cigarette vapour extract (ECVE) on a cytotoxicity, cellular functions and gene expressions in different human cell lines (adenocarcinoma cell line [A549] and human bronchial epithelial cells [HBEpCs]), primary mouse cells (murine alveolar epithelial typeII cells [mAECII] and pulmonary arterial smooth muscle cells [mPASMCs]) and human lung cells (human pulmonary arterial smooth muscle cells [hPASMCs]) as well as to study the long-term effects of e-cigarette vapour on the function and structure of mouse lung and pulmonary circulation in vivo.Regardless of nicotine, ECVE showed a little (A549, mAECII, and hPASMCs) or no effect (HBEpCs and mPASMCs) on the cell viability compared to the cigarette smoke extract (CSE). Furthermore, ECVE with (18mg/ml) or without nicotine did not alter the cellular respiration of mPASMC as well as the migration of hPASMC and mPASMC. However, only nicotine containing ECVE decreased the proliferation of hPASMC and mPASMC compared to ECVE without nicotine. The hypothesis driven approach showed increased mRNA expression of iNOS, Csf2, 5HTT and Ccna1 in mPASMC after exposure to ECVE with nicotine indicating their possible roles in ECVE nicotine-induced decrease of mPASMC proliferation. Non-hypothesis driven transcriptomic analysis by microarray revealed that genes related to cell cycle, DNA replication and spliceosome were upregulated, while genes of lysosome and metabolic pathways were downregulated in mPASMCs exposed to ECVE regardless of nicotine. Moreover, various metabolic pathways, particularly genes involved in cytochrome P450 and glutathione metabolism were upregulated in mAECII. Exposure of wild type mice (C57BL/6J) to e-cigarette vapour with (18mg/ml) or without nicotine for 8 months (6 hours/day, 5 days/week) did not result in development of neither lung emphysema nor pulmonary hypertension assessed by lung function, hemodynamic and morphological analysis, respectively. However, long-term exposure to e-cigarette vapour evoked changes in the neutrophils, lymphocytes and macrophages amounts in bronchoalveolar lavage fluid indicating that e-cigarette vapour could induce the alteration of immune cell dynamics in the mouse lungs.In conclusion, despite that ECVE is less cytotoxic compared to CSE, exposure to ECVE alters nicotine-independently various cellular signalling pathways in lung cells in vitro. Moreover, even though long-term exposure of mice to e-cigarette vapour does not show any functional and structural alterations in the lungs, similar to conventional CS, exposure to e-cigarette prompts the distinct inflammatory responses in the mouse lung. Further experiments are necessary to elucidate the effects of various puffing regimen parameters (e-cigarette topography) and especially the presence of numerous flavours in e-cigarette liquids on the human health.

Zigarettenrauchen (CS) ist die vermeidbare Hauptursache für chronisch obstruktive Lungenerkrankung (COPD) und Lungenkrebs. Die Erforschung potenziell weniger schädlicher Nikotinverabreichungsgeräte und Werkzeuge zur Raucherentwöhnung führte zur Entwicklung von elektronischen Zigaretten (E-Zigarette). Trotz des Fehlens geeigneter Studien über ihre Sicherheits-, Wirksamkeits- und Gesundheitsauswirkungen gewinnen E-Zigaretten als Ansatz zur Raucherentwöhnung an Popularität und die Zahl der E-Zigarettennutzer wächst schne11, vor allem bei jüngeren Generationen.Vor diesem Hintergrund wurden in dieser Arbeit die Auswirkungen von Dampfextrakten von E-Zigaretten (ECVE) auf die Zytotoxizität, Zellfunktion und Genexpression m unterschiedlichen Ze111inien (humane Lungenadenokarzinomze111inie [A549]; humane Bronchialepithelzellen[HBEpCs]), primären Mauszellen (alveolären TYP-II Epithelzellen der Maus [mAECII]; glatte Muskelzellen der Lungenarterie der Maus [mPASMC]) und humanen Lungenzellen (glatte Muskelzellen der Lungenarterie des Menschen [hPASMC]) untersucht. Weiterhin wurden Langzeiteffekte von ECVE auf die Lungenfunktion, Lungenstruktur und den Lungenkreislauf im Mausmode11 analysiert.Im Vergleich zu Dampfextrakten von herkömmlichen Zigaretten (CSE) hatte ECVE, mit oder ohne Nikotin, einen geringen (A549, mAECII und hPASMC) bzw. gar keinen (HBEpCs und mPASMCs) Effekt auf die Zelllebensfähigkeit. Weiterhin beeinflusste ECVE mit oder ohne Nikotin nicht die zelluläre Atmung von mPASMC und die Migration von hPASMC und mPASMC. Allerdings verringerte im Vergleich von ECVE mit oder ohne Nikotin nur nikotinhaltiger ECVE die Proliferation von hPASMC und mPASMC.Der hypothesengetriebene Ansatz zeigte die erhöhte mRNA-Expression von iNOS, Csf2, 5HTT und Ccnal in mPASMC nach Exposition gegenüber ECVE mit Nikotin und deutet auf eine mögliche Rolle in der, durch nikotinhaltigen ECVE induzierten, Abnahme der mPASMC Proliferation an. Die nicht hypothesengesteuerte transkriptomische Analyse von ECVE exponierten mPASMC-Zellen durch Microarray ergab, dass mit Zellzyklus, DNA-Replikation und Spleißosom assoziierte Gene hochreguliert, während lysosomale und Gene involviert in Stoffwechselwegen nikotinunabhängig herunterreguliert wurden. Darüber hinaus wurden in mAECII verschiedene Stoffwechselwege hochreguliert, insbesondere Gene, welche am Zytochrom P450- und Glutathionstoffwechsel beteiligt sind.Die Exposition von Wildtyp-Mäusen (C57BL/6J) gegenüber E-Zigarettendampf mit (18mg/ml) oder ohne Nikotin für 8 Monate (6 Stunden/Tag, 5 Tage/Woche) führte weder zur Entwicklung eines Lungenemphysems noch zu pulmonaler Hypertonie, welches anhand von Lungenfunktionstest und hämodynamischer bzw. morphologischer Analyse beurteilt wurde. Die langfristige Exposition gegenüber E-Zigarettendampf veränderte jedoch die Anzahl der Neutrophilen Granulozyten, Lymphozyten und Makrophagen in der bronchoalveolären Lavageflüssigkeit. Dies deutet darauf hin, dass E-Zigarettendampf die Dynamik der Immunzellen in der Lunge von Mäusen zu beeinflussen bzw. zu verändern vermag.Zusammenfassend lässt sich sagen, dass durch die Exposition zu ECVE nikotinunabhängig verschiedene zelluläre Signalwege in Lungenzellen gestört werden, aber ECVE im Vergleich zu CSE dennoch geringere zytotoxische Wirkung in vitro aufweist.Auch wenn die langfristige Exposition von Mäusen gegenüber E-Zigarettendampf keine funktionellen und strukturellen Veränderungen in der Lunge aufzeigte, ähnlich wie bei herkömmlichen Zigarettenrauch, lösen E-Zigaretten eindeutige Entzündungsreaktionen in der Lunge von Mäusen aus. Weitere Experimente sind absolut notwendig, um die Auswirkungen von unterschiedlichen Parametern des Puffingschemas und insbesondere das Vorhandensein zahlreicher Aromen in E-Zigarettenflüssigkeiten auf die menschliche Gesundheit zu ermitteln.
Keywords: ddc:610